ASPEK PENOLAKAN DALAM NOVEL GREAT EXPECTATIONS KARYA CHARLES DICKENS - Kekung, Indrianingsi; Lasut, Theresia M.C; Rambing, Rosalina (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2022)
ABSTRACT                                              Indrianingsi Kekung1                                    Dra. Theresia M.C. Lasut, M.Hum2                                      Dra. Rosalina R. Rambing, DEA3     This research is entitled "Rejection Aspect in the Novel Great Expectations by Charles Dickens." This research focuses on identifying and classifying the types of rejection and analyzing and describing the aspect of rejection found in every utterance of each character in the novel Great Expectations. Rejection acts is a perlocutionary act. This study uses the theory of Leech (1983) and Crystal (1978), in e collecting the data, the writer focuses on the utterances conveyed by each character in the novel. each datum was analyzed descriptively and the results showed that there were several aspects of direct rejection as many 26 data, and indirect rejection 19 data, namely: to get hearer to think, to get hearer to do something, to bring hearer to know, irritate, frighten, encourage, and amuse.________________________________________Key Words : Rejection, Novel : Great Expectations . Pragmatics.